Freedom dreaming with Black Canadian mothers - Fearon, Stephanie (Frontiers in Education, 2022)
A burgeoning body of literature explores the educational experiences of Black Canadian students. Such literature reveals Black students as disproportionately impacted by academic underachievement, discipline policies, and special education placement. Black Canadian mothers have long dreamt of and advocated for humanizing learning spaces for their children. This paper explores how a group of Black Canadian mothers partnered with one another to reimagine learning opportunities for their children. This article presents insights obtained from eight in-depth interviews with Black Canadian mothers living in Toronto. In these interviews, participants shared stories that center the following questions: How do Black mothers reconceptualize their motherwork to include freedom dreams? How do Black mothers partner with one another to produce a vision for their children’s education? Grounded in an arts-informed narrative methodology, this study compiled findings gained from interviews into the creative non-fiction story Set it Off. Set it Off captures personal narratives, shared by study participants, highlighting the central role of freedom dreams and resistance as Black Canadian mothers organize for their children’s education.